An Account of Interference in Associative Memory: Learning the Fan Effect. (5th January 2017) - Thomson, Robert; Harrison, Anthony M.; Trafton, J. Gregory; Hiatt, Laura M.
Abstract: Associative learning is an essential feature of human cognition, accounting for the influence of priming and interference effects on memory recall. Here, we extend our account of associative learning that learns asymmetric item‐to‐item associations over time via experience (Thomson, Pyke, Trafton, & Hiatt, 2015) by including link maturation to balance associations between longer‐term stability while still accounting for short‐term variability. This account, combined with an existing account of activation strengthening and decay, predicts both human response times and error rates for the fan effect (Anderson, 1974; Anderson & Reder, 1999) for both target and foil stimuli. Abstract : How does an architecture learn associations between memory items to facilitate cue‐based memory retrieval? Thomson et al. address this open question in the ACT‐R literature with a learning mechanism that balances short‐term and long‐term learning and decay, while accounting for a well‐studied phenomenon: the fan effect.